A study of personality of leader and style of his co-operation in sporting command - Smolar I.I; Ivashchenko E.A (Kharkov National Pedagogical University, 2012)
The personality features of leader of sporting command and style of his co-operation are considered. The problems of adjusting and optimization of co-operation of leader and other players of command are selected in achievement of the set team purpose. 37 skilled sportsmen-handballers took part in research. An informal structure is exposed in commands, leaders and followers are certain. The quantitative indexes of personality features of leader, follower of sporting command are certain. Style of co-operation of leader and follower (prevailing and goodwill) and quality is exposed personalities which will be realized by them in a sporting command. It is set that in interpersonality co-operation a leader will realize dominant style, and follower equal will realize dominant and benevolent styles.